2018
DOI: 10.1182/blood-2018-99-117209
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity Profile of Elotuzumab for Multiple Myeloma: A Systematic Review and Meta-Analysis

Abstract: Background: Elotuzumab (elo) is a humanized monoclonal antibody, which has been approved by the FDA for use in combination with lenalidomide (lena) and dexamethasone (dexa) in patients (pts) with relapsed and refractory multiple myeloma (RRMM). Elotuzumab is effective as a single agent, as well as in combination for multiple myeloma treatments, supporting the use of elo in pts with RRMM and newly diagnosed multiple myeloma (NDMM) pts. Method: After review of literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Humanized monoclonal antibody, elotuzumab (elo) has been shown to be effective as a single agent as well as combination form for the treatment of patients having multiple myeloma with RRMM and newly diagnosed multiple myeloma (NDMM). 24 Dinutuximub binds to surface GD2 and causes tumor regression through complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity. Patients having high-risk Neuroblastoma get aggressive chemotherapy and stem cell transplantation, leaving them immunocompromised.…”
Section: Resultsmentioning
confidence: 99%
“…Humanized monoclonal antibody, elotuzumab (elo) has been shown to be effective as a single agent as well as combination form for the treatment of patients having multiple myeloma with RRMM and newly diagnosed multiple myeloma (NDMM). 24 Dinutuximub binds to surface GD2 and causes tumor regression through complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity. Patients having high-risk Neuroblastoma get aggressive chemotherapy and stem cell transplantation, leaving them immunocompromised.…”
Section: Resultsmentioning
confidence: 99%
“…Among the mAbs, the anti-CD38 antibodies daratumumab 1 and isatuximab 3 are widely used for relapsed MM patients and are associated with a high response rate and superior prognosis. There is another mAb called elotuzumab, which is an antibody against signaling lymphocytic activation molecule F7 (SLAMF7) 5 . Elotuzumab is used with the combination of lenalidomide or pomalidomide in a relapsed setting 2 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There is another mAb called elotuzumab, which is an antibody against signaling lymphocytic activation molecule F7 (SLAMF7) 5 . Elotuzumab is used with the combination of lenalidomide or pomalidomide in a relapsed setting 2 , 5 , 6 . Elotuzumab is effective against SLAMF7-expressing myeloma via active immune cells, particularly natural killer cells 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There is another mAb called elotuzumab, which is an antibody against signaling lymphocytic activation molecule F7 (SLAMF7). 5 Elotuzumab is used with the combination of lenalidomide or pomalidomide in a relapsed setting. 2,5,6 Elotuzumab is effective against SLAMF7-expressing myeloma via active immune cells, particularly natural killer cells.…”
Section: Introductionmentioning
confidence: 99%
“…5 Elotuzumab is used with the combination of lenalidomide or pomalidomide in a relapsed setting. 2,5,6 Elotuzumab is effective against SLAMF7-expressing myeloma via active immune cells, particularly natural killer cells. 7,8 Although previous studies reported that elotuzumab showed a high response rate in relapsed MM patients, durable e cacy was achieved in only one fourth of the patients.…”
Section: Introductionmentioning
confidence: 99%